Anti-EGFR re-challenge with chemotherapy in RAS wild-type advanced colorectal cancer (A-REPEAT study): efficacy and correlations with tissue and plasma genotyping - J. Sgouros; A. Eliades; K. Papadopoulou; N. Korfiatis; D. Papamichael; E. Fountzilas; E. Tsolaki; A. Achilleos; K. Tsangaras; C. Loizides; G. Oikonomopoulos; T. Makatsoris; et al. (ESMO Gastrointestinal Oncology, 2025)
Background: Approved treatments for colorectal cancer (CRC) patients pretreated with two lines of therapy are of limited efficacy. Anti-epidermal growth factor receptor (EGFR) re-challenge might represent an option in RAS wild-type tumours. This study aimed to evaluate the efficacy of anti-EGFR re-challenge strategies (panitumumab/chemotherapy). Materials and methods: RAS wild-type metastatic CRC patients following first-line chemotherapy + anti-EGFR agent and second-line chemotherapy ± anti-vascular endothelial growth factor agent were eligible. Panitumumab with irinotecan or oxaliplatin-based chemotherapy was used. The primary objective was response rate (RR). Secondary objectives were safety, progression-free survival and overall survival. Next-generation sequencing-based genotyping in archived tissue and plasma was carried out to identify prognostic factors. Results: The study closed prematurely, due to poor accrual, with 23 patients included. Most patients had primary tumours in the left colon/rectum, and the liver was the most common metastatic site. Treatment modifications were required in 74% of patients due to side-effects primarily, neutropenia and acneiform rash. One patient died from hepatic failure. The objective RR in the intention-to-treat population was 13%, and the disease control rate (DCR) was 52%. Forty-eight percent of patients tested via liquid biopsy had RAS mutations before re-challenge with panitumumab despite a median interval from previous anti-EGFR therapy of 12 months. Control of disease did not correlate with the results of liquid biopsy. RR and DCR in patients without RAS mutations in liquid biopsies were 18.2% and 54.5%, respectively. Conclusion: Panitumumab/chemotherapy as an anti-EGFR re-challenge strategy had modest activity in our patient cohort.